The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fmicb.2017.00214
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Diversity Assessment of Indian Type-2-Diabetics Reveals Alterations in Eubacteria, Archaea, and Eukaryotes

Abstract: Diabetes in India has distinct genetic, nutritional, developmental and socio-economic aspects; owing to the fact that changes in gut microbiota are associated with diabetes, we employed semiconductor-based sequencing to characterize gut microbiota of diabetic subjects from this region. We suggest consolidated dysbiosis of eubacterial, archaeal and eukaryotic components in the gut microbiota of newly diagnosed (New-DMs) and long-standing diabetic subjects (Known-DMs) compared to healthy subjects (NGTs). Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
113
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(133 citation statements)
references
References 79 publications
14
113
5
1
Order By: Relevance
“…Unsupervised clustering by PLSDA indicated clear separation of Indian subjects from subjects of other countries. We would like to note here that the previous metataxonomic profiling study by Bhute et al indicated Prevotella, Lactobacillus, Lachnospira and Roseburia to be overrepresented in urban and rural Indian subjects from Delhi and Pune as compared to American subjects [31].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Unsupervised clustering by PLSDA indicated clear separation of Indian subjects from subjects of other countries. We would like to note here that the previous metataxonomic profiling study by Bhute et al indicated Prevotella, Lactobacillus, Lachnospira and Roseburia to be overrepresented in urban and rural Indian subjects from Delhi and Pune as compared to American subjects [31].…”
Section: Discussionmentioning
confidence: 62%
“…Bhute et al showed the presence of Firmicutes as the major phylum in Indian subjects; other major phyla included Bacteroidetes, Proteobacteria and Actinobacteria [31]. Their study also indicated that Prevotella and Megasphaera were dominant genera [31].…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…3). In NewDMs, Akkermansia, Blautia, and Ruminococcus showed significantly decreased abundance (P ϭ 0.0009 and log 2 FC ϭ Ϫ14.2, P ϭ 0.0009 and log 2 FC ϭ Ϫ2.52, and P ϭ 0.006 and log 2 FC ϭ Ϫ0.39, respectively), and a similar trend was observed for Prevotella (P ϭ 0.054 and not significant), one of the dominant genera found in Indian gut (19,21,22), while Lactobacillus (P ϭ 0.01 and log 2 FC ϭ 5.27) showed increased abundance compared to ND. Significantly increased abundance of Megasphaera (P ϭ 0.005 and log 2 FC ϭ 1.42), Escherichia (P ϭ 0.003 and log 2 FC ϭ 1.96), and Acidaminococcus (P ϭ 0.008 and log 2 FC ϭ 2.90) and decreased abundance of Sutterella (P ϭ 0.003 and log 2 FC ϭ Ϫ0.66), was observed in KnownDMs compared to ND.…”
mentioning
confidence: 57%
“…An abundance of Prevotella showed positive correlation with histidine (P ϭ 0.025). Prevotella is one of the most dominant genera found in the Indian gut (19,21,22) and is inversely correlated with glucose, HbA1c, triglycerides, VLDL cholesterol, HDL cholesterol, leucine, tyrosine, methionine, IL-6, and lipid peroxides and positively correlated with total antioxidants; however, these associations were not found to be significant (P Ͼ 0.05). An abundance of genus Akkermansia showed strong inverse correlation with fasting glucose (P ϭ 0.04), HbA1c (P ϭ 0.008), leucine (P ϭ 0.04), and tryptophan (P ϭ 0.002) and a strong positive correlation with histidine (P ϭ 0.006) and total anti- ).…”
Section: Downloaded Frommentioning
confidence: 99%